Equivalence of two different approaches to global gyrokinetic simulations - Parra, F; Barnes, M (2014)
A set of flux tube gyrokinetic equations that includes the effect of the spatial variation of the density, temperature and rotation gradients on the turbulence is derived. This new set of equations uses statistical periodicity as a boundary condition, avoiding the need to impose non-physical boundary conditions. This new approach to global gyrokinetic simulations is shown to be equivalent to the traditional global $δ f$ gyrokinetic equations when the turbulent eddies are smaller than the characteristic size of the machine.